2018
DOI: 10.1029/2018gc007609
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Pressure of Crystallization of Ca(OH)2: Implications for the Reactive Cracking Process

Abstract: Mineral hydration and carbonation can produce large solid volume increases, deviatoric stress, and fracture, which in turn can maintain or enhance permeability and reactive surface area. Despite the potential importance of this process, our basic physical understanding of the conditions under which a given reaction will drive fracture (if at all) is relatively limited. Our hydration experiments on CaO under uniaxial loads of 0.1 to 27 MPa show that strain and strain rate are proportional to the square root of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…For example, the replacement of mafic minerals with carbonates can result in an up to ∼ 44 % increase in solid molar volume (Goff and Lackner, 1998;Hansen et al, 2005;Kelemen and Matter, 2008) potentially clogging pore space, reducing permeability and increasing pore pressure. Alternatively, this volume expansion can generate stresses causing reaction-induced fracturing, which provides additional fluid pathways and maintains porosity and permeability for the reaction to proceed (Iyer et al, 2008;Jamtveit et al, 2009;Kelemen and Matter, 2008;Lambart et al, 2018;Macdonald and Fyfe, 1985;Renard et al, 2020;Rudge et al, 2010;Skarbek et al, 2018;Xing et al, 2018;Zhu et al, 2016). The fracturing behavior itself is affected by the fluid chemistry via kinetic reduction of fracture energy due to fluid absorption on mineral surfaces and crack tip blunting (Baud et al, 2000;Orowan, 1944;Rutter, 1972;Scholz, 1968), and activation of fluid-promoted stress corrosion processes such as subcritical crack growth resulting in time-dependent deformation, which is the focus of this paper (Anderson and Grew, 1977;Atkinson, 1984;Atkinson and Meredith, 1987;Brantut et al, 2013;Nara et al, 2013;Rice, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the replacement of mafic minerals with carbonates can result in an up to ∼ 44 % increase in solid molar volume (Goff and Lackner, 1998;Hansen et al, 2005;Kelemen and Matter, 2008) potentially clogging pore space, reducing permeability and increasing pore pressure. Alternatively, this volume expansion can generate stresses causing reaction-induced fracturing, which provides additional fluid pathways and maintains porosity and permeability for the reaction to proceed (Iyer et al, 2008;Jamtveit et al, 2009;Kelemen and Matter, 2008;Lambart et al, 2018;Macdonald and Fyfe, 1985;Renard et al, 2020;Rudge et al, 2010;Skarbek et al, 2018;Xing et al, 2018;Zhu et al, 2016). The fracturing behavior itself is affected by the fluid chemistry via kinetic reduction of fracture energy due to fluid absorption on mineral surfaces and crack tip blunting (Baud et al, 2000;Orowan, 1944;Rutter, 1972;Scholz, 1968), and activation of fluid-promoted stress corrosion processes such as subcritical crack growth resulting in time-dependent deformation, which is the focus of this paper (Anderson and Grew, 1977;Atkinson, 1984;Atkinson and Meredith, 1987;Brantut et al, 2013;Nara et al, 2013;Rice, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Completely carbonated (listvenites) and hydrated (serpentinites) peridotites are, however, frequently observed in outcrops, Reaction-driven cracking has been observed in experiments involving both carbonation of olivine (Xing et al, 2018;Zhu et al, 2016) and hydration of magnesium oxide (Zheng et al, 2018). Other experiments on analogue systems have demonstrated that hydration reactions involving lime (Lambart et al, 2018;Wolterbeek et al, 2018) and bassanite (Skarbek et al, 2018) can produce significant crystallization-induced stresses. However, the conditions under which positive feedbacks (cracking) overcome negative feedbacks (clogging) remain relatively uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experiments show that chemical reactions involving an increase in solid volume in a confined space can under certain conditions generate mechanical stresses on the confining boundariesa phenomenon known as the development of a 'force of crystallization' or 'crystallization pressure' (Becker and Day, 1905;Correns, 1949;Weyl, 1959;Schuiling and Wensink, 1962;Ostapenko, 1976;Wolterbeek et al, 2018). Recent studies have shown that certain mineral reactions are capable of generating stresses exceeding 150 MPa under laboratory conditions (Lambart et al, 2018;Skarbek et al, 2018;Wolterbeek et al, 2018;Zheng et al, 2018). This crystallization force is thought to be an important factor in a variety of geological processes, including mineral vein formation (Taber, 1916;Fletcher and Merino, 2001;Merino et al, 2006;Means and Li, 2001;Gratier et al, 2012), (pseudomorphic) mineral replacement (Maliva and Siever, 1988;Merino and Dewers, 1998;Fletcher and Merino, 2001;Putnis, 2009), spheroidal weathering (Røyne et al, 2008) and reaction-driven fracture (Jamtveit et al, 2008;Plumper et al, 2012;Putnis et al, 2009;Kelemen and Hirth, 2012;Van Noort et al, 2017).…”
Section: Introductionmentioning
confidence: 99%